Abnormal functional connectivity based on nodes of the default mode network in first-episode drug-naive early-onset schizophrenia. (January 2021) - Peng, Yue; Zhang, Sen; Zhou, Youqi; Song, Yichen; Yang, Ge; Hao, Keke; Yang, Yongfeng; Li, Wenqiang; Lv, Luxian; Zhang, Yan
Highlights: We believe that two aspects of this manuscript will make it interesting to general reader of your journal. On the one hand, Early-onset schizophrenia (EOS) is defined as schizophrenia beginning before the age of 18 years. Neurodevelopmental abnormality in EOS may shed light on the pathogenesis of illness. However, little is known about the profile of brain change in this specific patient group. We hypothesized that patients with EOS would have aberrant intra-network and inter-network functional connectivity (FC) in DMN in the resting state and that abnormal FC in DMN was associated with the clinical symptoms of schizophrenia. The aim of the present study is to examine FC of DMN at rest in antipsychotic-naive adolescents with first-episode schizophrenia. On the other hand, to the best of our knowledge, the current study firstly used regions of interest (ROI) method to detect the FC of DMN in drug-naïve and first-episode EOS patients. Our results provide evidence for abnormal FC in first-episode drug-naive EOS. These findings highlighted the importance of DMN in the pathophysiology of schizophrenia and provided insights into its etiology and pathogenesis. Abstract: Schizophrenia is considered a connectivity disorder. Further, the functional connectivity (FC) of the default-mode network (DMN) has gained the interest of researchers. However, few studies have been conducted on the abnormal connectivity of DMN in early-onset schizophrenia (EOS). In this study, the key brain regions of the DMN were used as seed regions to analyze the FC of the whole brain in EOS. When the seed was located in the medial prefrontal cortex (mPFC), patients with EOS exhibited decreased FC between mPFC and other brain regions compared with healthy controls (voxel P value < 0.001, cluster P value < 0.05, Gaussian random field corrected). When the seed was located in the posterior cingulate cortex (PCC), the FC between PCC and other brain regions was enhanced and weakened (voxel P value < 0.001, cluster P value < 0.05, Gaussian random field corrected), and PCC connectivity with the right parahippocampal gyrus was associated with Positive and Negative Syndrome Scale scores for the general score ( r = −0.315, P = 0.02). The results showed that the FC within the DMN and that between DMN and visual networks were abnormal, suggesting that the DMN might be involved in the pathogenesis of EOS.